Place Perspectives on a Postcard Installation - Creagh, Robyn (Black Swan Press, 2013)
Considering works of architecture as design-objects does not engage sufficiently with architecture as it is experienced by those who occupy or use it. Other perspectives are needed to understand architecture as part of embodied experience. This chapter considers an installation of postcards within a postgraduate conference from four perspectives to gain a more grounded understanding of the installation as occupied. With the support of a visual essay, this chapter takes each of the following perspectives in turn to gain richer insight into the participants experience of the installation; place as design-object, place as communication, place as lived space, and place as a moment in a network of relationships. Through this process a richer understanding of the installation is achieved. This richness is not available when considering any inhabited design solely as design-object. This inquiry is significant in providing a viable approach for architecture to engage with spaces as lived.